1955
DOI: 10.3109/00016925509171308
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral reflux in normal infants

Abstract: G u i d o I a n n a c c o n e and P a o l o E m. i l i o P a n z i r o n i Ureteral reflux of the vesical content occurs when the vesico-ureteral valve mechanism is impaired and the intravesical pressure prevails on the pyelo-ureteral excretory pressure. In normal conditions urine backilow from the bladder into the ureters is prevented mainly by the following factors: a) ureteral tonus and contractions, which make the intra-ureteral pressure greater than that of the resting bladder; b) the considerable length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Iannaccone (1966) found transient reflux very rarely in very small normal babies, and this has also been our experience, but as a rule it should be regarded as an abnormal finding. The cause of reflux is not clearly established.…”
Section: Ureteric Refluxsupporting
confidence: 74%
See 1 more Smart Citation
“…Iannaccone (1966) found transient reflux very rarely in very small normal babies, and this has also been our experience, but as a rule it should be regarded as an abnormal finding. The cause of reflux is not clearly established.…”
Section: Ureteric Refluxsupporting
confidence: 74%
“…It is now well established that reflux is abnormal at any age (Gibson, 1949;Iannaccone & Pazironi, 1955;Jones & Headstream, 1958;Leadbetter, Duxbury & Dreyfuss, 1960;Lich et al, 1964). Iannaccone (1966) found transient reflux very rarely in very small normal babies, and this has also been our experience, but as a rule it should be regarded as an abnormal finding.…”
Section: Ureteric Refluxsupporting
confidence: 64%
“…The precise incidence of VUR at birth is uncertain, because the invasive nature of cystography precludes examining normal babies, although it has been estimated at 2% [28]. However, six studies in infants (and some older children), from a time when such research was considered ethical, showed reflux in only 4 of 456 (0.9%) normal subjects, of which 3 were unilateral [29,30,31,32,33,34]. It seems reasonable to round the estimate up to 1% because the few older subjects may have had reflux and outgrown it.…”
Section: Why Maturation Cannot Occurmentioning
confidence: 99%
“…In two series of normal newborns subjected to cysto graphy only 1 out of 76 infants was found with transient reflux [7,8]. In another series, which did not specify the technique of cystography used, reflux was found in 55% of infants under 1 year of age [9], Despite this observation …”
Section: Radiological Assessmentmentioning
confidence: 96%